Do rise in housing prices push down childbirth decisions? - Han, Hui Lee (2018)
The increasing number of countries experiencing sub-replacement fertility level suggests a shift in global fertility behaviour. This paper aims to investigate the causal effect of housing price level on fertility rate by devising a series of empirical strategies to address various endogeneity issues. Using panel data method, unobserved country-specific time invariant characteristics will be controlled for to isolate the effect of housing prices. An identification strategy involving two unique instruments is deployed to address the presence of simultaneous endogeneity. Finally, the GMM dynamic panel method is used to address dynamic endogeneity arising from effects of macro-prudential policies. The results from using the proposed empirical strategies show that housing prices have a significant effect on fertility rate. This suggests that housing prices do play a role in childbearing decisions as the cost competition between housing and childbearing forces couples to postpone or forgo family formation plans.